2022
DOI: 10.21203/rs.3.rs-2233134/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroprotective effects of morroniside against Parkinson's Disease via inhibiting oxidative stress and ferroptosis

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disorder after Alzheimer disease accompanied by the death of dopaminergic neurons and brain nigrostriatal mitochondrial damage in the elderly population. The features of the disease include tremor, rigidity, postural instability, and motor retardation. The pathogenesis of Parkinson’s disease is complex, and abnormal lipid metabolism resulting in ferroptosis due to the excessive accumulation of free radicals from oxidative stress in the substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…51 The specific inhibitor of Nrf2, ML385, significantly inhibited FTH1 and Fpn1 in PC12 cells treated with MPP + (1-methyl 4-phenyl pyridinium), a classical model of Parkinson's disease. 52 In other words, the modulation of Nrf2 on ferritin and Fpn1 should be synchronous. The disruption of Nrf2 cannot fully explain https://doi.org/10.2147/DDDT.S458013…”
Section: Discussionmentioning
confidence: 99%
“…51 The specific inhibitor of Nrf2, ML385, significantly inhibited FTH1 and Fpn1 in PC12 cells treated with MPP + (1-methyl 4-phenyl pyridinium), a classical model of Parkinson's disease. 52 In other words, the modulation of Nrf2 on ferritin and Fpn1 should be synchronous. The disruption of Nrf2 cannot fully explain https://doi.org/10.2147/DDDT.S458013…”
Section: Discussionmentioning
confidence: 99%
“…GSH exists not only in the cytoplasm but also in mitochondria, and protects mitochondria from oxidative stress by scavenging ROS generated during electron transport and oxidative phosphorylation within mitochondria (Jacobs and Riemer, 2023). Recently, Li et al (2023) found that morroniside can reduce ROS production by restoring the mitochondrial respiratory chain in a Parkinson's disease model. Our results using Mito-SOX showed that morroniside effectively attenuated H2O2-induced mitochondrial superoxide production, corresponding to major mtROS (Fujii et al, 2022;Jomova et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the anti-cytotoxic effect of morroniside in response to H2O2 treatment was associated with preservation of SOD activity, inhibition of calcium (Ca 2+ ) accumulation, and blockade of mitochondrial membrane potential (MMP) reduction (Wang et al, 2009). Morroniside also prevented brain injury following focal cerebral ischemia by protecting oxidative stress and apoptosis (Wang et al, 2010), and was proven to have similar efficacy in models of Alzheimer's (Chen et al, 2023) and Parkinson's disease (Li et al, 2023). Recently, we reported that heme oxygenase-1 activation by morroniside plays a crucial role in minimizing oxidative and inflammatory damage in lipopolysaccharide-challenged macrophages (Park et al, 2021).…”
mentioning
confidence: 99%
“…Et zucc, attenuates ROS-mediated mitochondrial damage in the treatment of Parkinson's. 123 Its hair growth-promoting effects have long been reported. 120 Therefore, it is reasonable to believe that these natural compounds in the tables can intervene in the hair cycle transition by counteracting OS in the HF, but their specific molecular mechanisms need to be further investigated.…”
Section: Modelmentioning
confidence: 99%
“…Then, a recent study found that morroniside, a natural compound from Cornus officinalis sieb. Et zucc , attenuates ROS‐mediated mitochondrial damage in the treatment of Parkinson's 123 . Its hair growth‐promoting effects have long been reported 120 .…”
Section: Therapeutic Strategiesmentioning
confidence: 99%